Myxolipoma of the Popliteal Fossa: A Rare Tumor Case Report - Yuchen You; Jessica Cao; Brandon Nguyen; Melanie Gero; Karim Jreije (Reports)
Myxolipomas are rare variants of lipomas characterized by abundant myxoid changes resulting from an abundant mucoid component. While myxolipomas have been reported in various anatomical locations, their occurrence in the popliteal fossa is exceptionally rare, with the last published case dating back to 1914. We present a case of a 64-year-old male with a large myxolipoma in the popliteal region. The patient underwent successful surgical excision, and a histopathological examination confirmed the diagnosis of myxolipoma. This case report highlights the clinical features, differential diagnosis, and diagnostic challenges associated with myxolipomas in the popliteal fossa.